Minimally Invasive-Closed Reduction and Percutaneous Pinning for Supracondylar Fractures of the Humerus in Children - Pradhan, Nabees Man Singh; Tamrakar, Rojan; Gyawali, Bidur; Bhatta, Toya Raj; Acharya, Balakrishnan M.; Shrestha, Suman; Shrestha, Saroj Krishna; Rajbhandari, Achyut; Shrestha, Utsab (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Although Closed Reduction and Percutaneous Pinning is the gold standard of treatment for Supracondylar fractures (SC) in children, reduction is not always easy. Minimally Invasive, Closed Reduction and Percutaneous Pinning (MI-CRPP) reduces the soft tissue trauma and provides easy reduction. We have reviewed the success rate of minimally invasive reduction technique and its outcome.Methods: We reviewed the charts of 155 children (97 male, 58 female) age ranging from 2 to 14 years with SC fractures of the humerus who were operated with minimally invasive closed reduction and precutaneous pinning from November 2008 to June 2014 at Patan Hospital and Om Hospital. They were followed up for a mean of eight (4 to 24) weeks. The K-wires were removed at 4 to 6 (average 4.28) weeks.Results: Male children were affected more than female with the ratio being 97 to 58. Right side was affected more than left (ratio 89 to 66). Post-operatively, there were six (3.87%) ulnar nerve injury and eight (5.16%) patients came with superficial pin tract infection. One hundred and thirteen (72.9%) had excellent, 35 (22.58%) good, five (3.23%) fair and two (1.3%) poor results at the eight week follow-up which was improved to 144 (92.9%) excellent, seven (4.5%) good, three (1.9%) fair and one (0.65%) poor results at the 14 week follow-up.Conclusions: Closed reduction of supracondylar fractures of the humerus in children with minimally invasive technique prior to K-wire fixation is a relatively simple, safe and effective method of achieving satisfactory reduction and good functional outcome.